Educational climate in medical residency - Sarabia-Arce, Silvana (2019)
The educational climate is a concept that must be relevant to all of those involved in the teaching-learning process, it is important for both students and medical teachers. This article will review the areas involved in the educational climate, the tools used to assess it and will highlight the potential impact of the educational climate to promote, stimulate, optimize and improve the quality of the educational experience of the students.